Respuesta :

Answer:

x = 5

y = -2

Explanation:

2x + y = 8

y= x - 7

We need are solving for x, and we know what y is

We need to substitute the y equation for y in the first equation

2x+x-7=8

Step 1: Simplify both sides of the equation.

2x+x−7=8

2x+x+−7=8

(2x+x)+(−7)=8(Combine Like Terms)

3x+−7=8

3x−7=8

Step 2: Add 7 to both sides.

3x−7+7=8+7

3x=15

Step 3: Divide both sides by 3.

3x / 3 = 15 / 3

x = 5

Solve for y

2x + y = 8

2 * 5 + y = 8

Step 1: Simplify both sides of the equation.

(2)(5)+y=8

10+y=8

y+10=8

Step 2: Subtract 10 from both sides.

y+10−10=8−10

y=−2